2017
DOI: 10.1016/j.jare.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C and kidney disease: A narrative review

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 93 publications
3
46
0
6
Order By: Relevance
“…O mecanismo de lesão vascular é tipicamente atribuído ao C1q, componente ativo do complemento incorporado ao complexo da crioglobulina. Assim, a lesão endotelial ocorre pela ativação da cascata do complemento através da via clássica, bem como pela ligação a receptores do complemento no endotélio 7 . A ativação do complemento gera fatores quimiotáticos como C3a e C5a, que recrutam e ativam leucócitos pró-inflamatórios.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…O mecanismo de lesão vascular é tipicamente atribuído ao C1q, componente ativo do complemento incorporado ao complexo da crioglobulina. Assim, a lesão endotelial ocorre pela ativação da cascata do complemento através da via clássica, bem como pela ligação a receptores do complemento no endotélio 7 . A ativação do complemento gera fatores quimiotáticos como C3a e C5a, que recrutam e ativam leucócitos pró-inflamatórios.…”
Section: Discussionunclassified
“…A ativação do complemento gera fatores quimiotáticos como C3a e C5a, que recrutam e ativam leucócitos pró-inflamatórios. Isso também leva à formação de C5-9 e por fim do complexo de ataque a membrana, que tem um papel importante no dano endotelial 7 . Também deve-se considerar o efeito direto do vírus sobre as células endoteliais 5 , uma vez que o antígeno do HCV foi identificado nos glomérulos sem anticorpos detectáveis por ensaios como ELISA, ou mesmo por replicação viral no sangue periférico através da reação em cadeia da polimerase.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…121 Although early case series suggested that posttransplant patient and allograft outcomes for HCV-positive patients were similar to HCV-negative recipients, more contemporary data and metaanalyses have indicated that outcomes are in fact worse. 123 Allograft survival is also negatively affected by recipient HCV-positive status with a metaanalysis reporting a hazard ratio (HR) of 1.7 (95% CI, 1.46 to 2.11) for graft loss, but not all studies have consistently shown a negative effect of HCV infection on kidney allograft survival. 123 Allograft survival is also negatively affected by recipient HCV-positive status with a metaanalysis reporting a hazard ratio (HR) of 1.7 (95% CI, 1.46 to 2.11) for graft loss, but not all studies have consistently shown a negative effect of HCV infection on kidney allograft survival.…”
Section: Kidney Transplantation In Hepatitis C Virus-positive Patientsmentioning
confidence: 99%